ENTREPRENEURIAL INNOVATION AND POVERTY ALLEVIATION IN FEDERAL CAPITAL TERRITORY, ABUJA, NIGERIA (Journal of Global Accounting, 2025)
This study examined entrepreneurial innovation as an effective tool for poverty alleviation in Federal Capital Territory (FCT), Abuja. A survey research design was adopted, and a structured questionnaire was used to elicit response from a sample of 109 respondents, selected through a purposive sampling technique to ensure the inclusion of individuals with relevant experiences in entrepreneurship. The data sourced was subjected to analysis in both descriptive statistics using percentages, and inferential statistics using regression tool from Statistical Product for Social Science (SPSS) version 27. The findings indicated that entrepreneurial innovation significantly contributes to creating employment opportunities for residents of FCT Abuja. The results of the one-sample t-test demonstrated a substantial mean difference from the assumed mean of zero, with a t-value of 23.650 and a significance level of p
Keywords: Entrepreneurial Innovation; Effective Tool; Poverty Reduction